Trữ lượng nước dưới đất vùng Hà Nội và định hướng điều tra, đánh giá khai thác sử dụng - Đản, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
SUMMARYGroundwater resources in Hanoi and orientation for investigation and utilisationThe expanded Hanoi area is large, but the investigation levels are different. Only in the old area (921 km2 area), assessment of groundwater (GW) reserves has been done, with high waterpotential. The potential GW reserves is about 6 million m3 per day which are mainly in quaternary sediments, specially in Pleistocene aquifer (qp) for water demand of the Capital. The exploitable GWreserves is 837,000 m3 per day, occupying only 14 % of potential value. The GW investigation should be done, specially for detailed investigation in order to meet the requirement of the Capital’s water demand. In other hand, the investigation should be done to protect GW that degradation has been identified.